Eating fire : my life as a lesbian avenger - Cogswell, Kelly (University of Minnesota Press, 2014)
When Kelly Cogswell plunged into New York's East Village in 1992, she had just come out. An ex-Southern Baptist born in Kentucky, she was camping in an Avenue B loft, scribbling poems, and playing in an underground band, trying to figure out her next move. A couple of months later she was consumed by the Lesbian Avengers, instigating direct action campaigns, battling cops on Fifth Avenue, mobilizing 20,000 dykes for a march on Washington, D.C., and eating fire-literally-in front of the White House. At once streetwise and wistful, Eating Fire is a witty and urgent coming-of-age memoir spannin.